The Geopolitical Complexity of Medieval Islam: Dynastic Conflicts Among the Safawid, Mamluks, and Ottoman - Zaki Azmirrijali (Universitas Islam Negeri Sumatera Utara, 2026)
From the 14th to the 17th centuries, the conflict between Muslims escalated. This conflict occurred between three major Islamic powers: the Ottomans, the Safavids, and the Mamluks. These three opposing forces possessed significant power and influence. The purpose of this article is to explain the geopolitical conflict that occurred between these three powers. Using library research methods, several sources describing this conflict were identified. From the sources collected, differences in the characteristics of the three powers were identified. The Ottomans, with their Sunni-Muslim ideology, contrasted with the Shia-based Safavids. Meanwhile, the Mamluks, with their own objectives, exploited the conflict between the Ottomans and the Safavids. In the conflict between the three powers, the Ottomans emerged as the most powerful force, under the Mamluk rulers, and repelled the Safavids.